The phytotoxicity effect of fungicide-zinc/aluminium-layered double hydroxide nanocomposite on germinated palm oil seeds - Mustafa, Isshadiba Faikah; Hussein, Mohd Zobir; Abu Seman, Idris; Zainol Hilmi, Nur Hailini (2018)
Fungicides namely hexaconazole (HC) and dazomet (D) were successfully intercalated separately into the zinc/aluminium-layered double hydroxide (ZALDH) interlayers via the ion exchanged method. The resulting nanocomposites, hexaconazole-ZALDH (HZALDH), dazomet-ZALDH (DZALDH) and their commercially available counterparts; HC and D were used to study their effects on the oil palm seedlings growth. The phytotoxicity results showed that both HZALDH and DZALDH treatments gave positive effects on all the parameters tested. Most of the treatments gave almost similar seedling height of 50 % compared to the control. The HC treatment resulted in the lowest value in all the parameters used in this study, showing that the growth of the seedlings under this treatment was significantly inhibited.